Effect of salt to the lamellar phase swelling of DODAC and DODAB - Natasha, Maria Cresentia (Nanyang Technological University, 2020)
The unique self-assembling properties of surfactants in aqueous systems is essential for various applications, driven by the geometry of surfactants. Amongst the different types of surfactants, the cationic surfactant is an amphiphilic molecule that has shown to forms a lamellar phase structure. In the past few years, there are rigorous studies to investigate these surfactants’ phase behaviour under different conditions, such as by the addition of additives, salt or anionic surfactants. The interest is due to the unique behaviour of the lamellar structure. It is found that the lamellar gel phase exists below the transition temperature and lamellar liquid crystalline phase above the transition temperature. For instance, a hair conditioner utilises the lamellar liquid crystalline as it exhibits swelling properties. These lamellar layers facilitate the dispersion of non-polar additives and the conditioning compounds deposition. Hence, the transition temperature is crucial for surfactant applications.This study investigates the effect of salt: dioctadecyldimethylammonium chloride (DODAC) in the presence of sodium chloride (NaCl) and dioctadecyldimethylammonium bromide (DODAB) in the presence of sodium bromide (NaBr). The surfactant-salt-water system is studied for the change of the phase transition temperature and the surfactant packing parameter at different concentrations of salt and surfactant. Naked eye observation was done and followed by the detection of the surfactant birefringence using a polarized optical microscope (POM). DSC is used to analyse the thermal properties of the surfactant systems. Then, the packing structure was further investigated using the small/ wide-angle Xray scattering (SWAXS). The results show that the thermal transition of the DODAC-salt water system had no significant change as compared to the DODAC-water system. Interestingly, there was a slight increase in the transition temperature of DODAB-salt-water system. In terms of the transition reaction process, this study suggests that the reaction was facilitated as the enthalpy decreased upon the addition of salt. This study proves that the addition of salt can alter the phase behaviour of the surfactants.